KELAYAKAN ASPEK MEDIA DAN BAHASA DALAM PENGEMBANGAN BUKU AJAR DAN MULTIMEDIA INTERAKTIF BIOLOGI SEL - Dini Safitri; Tri Asih Wahyu Hartati (Florea : Jurnal Biologi dan Pembelajarannya, 2016)
Instructional materials are supporting the success of learning. The purpose is the development of teaching materials to help facilitate the learning process so that learners drafting special requirements that must be met. One of the compulsory subjects in biology education courses are of Cell Biology, and based on the needs analysis, multimedia-assisted teaching materials is very required. This research aims to develop products Cell Biology course textbook aided interactive multimedia using the 4D model viable aspect kegrafikan (media) and language. The 4D model consists of stages define, design, develop, and disseminate. The development phase is limited to stages develop. This research generates results media and language as validation data. The tests showed that the textbook and interactive multimedia eligible for use in the real learning of Biology Cell course.Validator also put forward suggestions for the improvement of some parts of teaching materials.